Effect of in-situ activated core-shell particles on fatigue behavior of carbon fiber reinforced thermoplastic composites - Sharma, Anurag (2024)
In this unique study, the effect of adding core-shell particles (CSPs) on fatigue performance of carbon-fiber reinforced PA6 (CF-PA6) laminates is investigated. The thermoplastic laminates were prepared using compression molding and were reinforced at ply interfaces with 2 wt% and 4 wt% CSPs of the polymer mass. A manual method was used to disperse CSPs using a sieve and carefully selected process parameters. The cyclic tests were conducted and assessed, considering S–N curve, stiffness degradation, and energy dissipation. Consequently, the fatigue life of modified composites improved respectively by eight and four times when 2 wt% and 4 wt% CSPs were used. The results showed that an optimal improvement was achieved with a 2 wt% CSPs. The fatigue strength coefficient and fatigue strength exponent of CF-PA6 composites improved by 22.13 % and 9.85 %, respectively. The findings have the potential to establish a new frontier in thermoplastic research and would help designers to enhance the fatigue properties of thermoplastic laminates in specific elastic tailoring structures.